The Role of Cytokines in Postmenopausal Osteoporosis; Relationship with Estrogen, Bone Density and Turnover Biomarkers - Gül Soykan; Peyman Yalçın (Archives of Rheumatology, 2006)
Objective: Estrogen deficiency probably induces increase of some cytokines (IL-1β, IL-2, IL-6, IL-8, TNF-α) that play role in bone resorption. The aim of our study was to determine the role of the cytokines in the etiopathogenesis of postmenopausal OP and its relationship with estrogen level, bone mineral density and bone turnover markers. Patients and Methods: The study group consisted of 108 subjects, 72 postmenopausal and 36 premenopausal women aged 30-85 years. The postmenopausal women were divided into 2 groups according to the presence of osteoporosis. Serum levels of cytokines (IL-1β, IL-2, IL-6, IL-8, TNF-α), estrogen, osteocalcin and urinary levels of deoxypyridinoline (DOP) were measured. Bone mineral density (BMD) of the lumbar spine and femur neck were measured by dual-energy X-ray absorbtiometry (DEXA). Results: Generally a decrease in estrogen level and an increase in cytokine production were observed in postmenopausal women. There was no significant differences between the groups with respect to levels of IL-1β, IL-2 ve IL-8 (p>0.05). The level of IL-6 was significantly higher in the osteoporotic group compared to the other groups (p<0.001). Postmenopausal women had higher values of TNF-α compared to the premenopausal women. There was no significant difference between the osteoporotic group and non-osteoporotic group (p>0.05). The groups didn’t significantly differ with respect to serum estrogen and cytokine levels (p>0.05). In premenopausal women, a negative correlation was observed between IL-1β and lomber BMD values (r=-0.445, p=0.031). In postmenopausal osteoporotic group, a negative correlation was found between IL-1β and DOP levels (r=-0.423 p=0.016). Significant positive correlations were found between IL-2 (r=0.437, p=0.018), IL-6 (r=0.413, p=0.026) and osteocalcin in premenopausal women. Conclusion: It is concluded that levels of IL-6 abd TNF-α show an increase together with a decrease in estrogen levels in postmenopausal women. Cytokines however, don’t seem to have relationship with the levels of estrogen, BMD and bone turnover markers. (Rheumatism 2006; 21: 49-55)